Grape Fruit Waste Compost as a Nursery Substrate Ingredient for High-Quality Cucumber (Cucumis sativus L.) Seedlings Production. Issue 4 (2nd October 2019) - Bayoumi, Yousry A.; El-Henawy, Ahmed S.; Abdelaal, Khaled A. A.; Elhawat, Nevien
Abstract: Greenhouse experiments were conducted to evaluate the utilization of compost derived from grape fruit waste (GFW) as an ingredient in nursery substrates for germination and development of cucumber. A randomized complete block design was used with thirteen treatments (S1-S13) encompassing 100% composted GFW, 60% GFW + 40% poultry manure including hardwood sawdust, 80% GFW + 20% broad bean straw, 80% GFW + 20% poultry manure including wheat straw, 50% coco peat + 50% vermiculite (as a control) and different combination of GFW-based composts with either coco peat or vermiculite. The resulted illustrated that GFW mixed with broad bean straw and poultry manure regardless of its source improved the chemical properties of composted GFW. Composts of GFW were even richer in nutrients, i.e., N, P, K, organic matter, soluble cations and anions and C/N ratio than control (50% coco peat + 50% vermiculite) except pH and electrical conductivity (EC), which was lower. Concentration of Cu, Fe, Cd and Pb were significantly lower in GFW composts than control substrate; while total phenolic content was significantly the highest in single compost of GFW. Mixing GFW composts with either vermiculite or coco peat (at 1:1 ratio by volume) was optimal for seed germination and seedling growth parameters; those combined substrates showed the highest FGP, CGRI, survival rate, and growth parameters in most cases. The negative effects of singly GFW compost can be removed or improved by mixing it with coco peat or vermiculite, so seed germination, seedling growth and survival rate significantly enhanced with mixing GFW-compost with coco peat or vermiculite substrates at ratio of 1:1. These recycled wastes are low cost products that can be usefully used in horticultural nurseries on a commercial scale. Highlights: Grape fruit waste compost had similar chemical properties to coco peat and vermiculite mixture Grape fruit waste compost had the highest total phenolic content Replacing coco peat or vermiculite by GFW compost enhanced seed germination of cucumber Mixing GFW compost with either coco peat or vermiculite improved seedling development of cucumber Replacing coco peat or vermiculite by GFW compost reduced the cost by 50%